Analysis of the first two waves of thymus homing stem cells and their T cell progeny in chick-quail chimeras (The Rockefeller University Press, 1989)
Chick-quail chimeras were used to study precursor/progeny relationships of hemopoietic stem cells (SC) that enter the embryonic thymus in waves to give rise sequentially to the TCR-1+, TCR-2+, and TCR-3+ lineages of T cells. The first wave of SC and their progeny were examined by grafting thymus from 9-d chick embryos (E9) into E3 quails. mAbs specific for chick T cell antigens were used to trace the development of T cells in the recipients. All three lineages of TCR-bearing cells were generated from the first wave of SC. The cortico-medullary transit time was several day shorter for the TCR-1 subpopulation than for the TCR-2 subpopulation, and the peripheral seeding of TCR-2 cells also occurred later in development. The duration of thymocyte production from the first wave of SC that entered the thymus was approximately 3 wk, during which gradual cortical to medullary replacement by second wave SC progeny occurred. When the latter was examined, after transplantation of E7 quail thymus into E3 chick embryos, a sequential generation pattern for the TCR-1 and TCR-2 cell progeny was not evident. Finally, recirculation of T cells to the thymus medulla was defined in this avian model.